Environmental damage costs from airborne pollution in the major cities in China - Wei, J.; Zhao, D.; Jia, R.; Marinova, Dora (Inderscience Publishers, 2009)
This paper estimates the environment external costs due to air pollutants via the impacts pathway approach used for ExternE project in the major cities in China over the period 2003-2006. The estimation results show that the external costs were US$ 20.15 billion in 2006, representing 2.28% of gross domestic product (GDP). This means that China suffered a lot for the air pollutants with the development of the economy. In the composition of external costs, damages to human health are the effects that generate the major part of externalities associated with air pollutants in these cities. The trend of external costs representing GDP in the sum of major cities was declining from 2003 to 2006, though the group in risk and agricultural products was increasing. Based on these finding, effective environmental policies and plans for economic development in these cities should focus not only on the volume of pollutants emission of SO2 and PM10, but also take other impact factors into account.